2005
DOI: 10.4269/ajtmh.2005.72.423
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of Human Dna by Primers Targeted to Leishmania Kinetoplast Dna and Post-Genome Considerations in the Detection of Parasites by a Polymerase Chain Reaction

Abstract: We evaluated the Leishmania Viannia-specific primers B1-B2 to detect Leishmania in normal skin and peripheral blood monocytes of patients with active cutaneous leishmaniasis. Southern blotting and sequencing of polymerase chain reaction (PCR) products confirmed the specificity of kinetoplast DNA (kDNA) amplification from tissue fluid from healthy skin, whereas the PCR with monocytes also amplified a human sequence of a size similar (718 basepairs) to the expected kDNA product (750 basepairs), resulting in fals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 17 publications
2
29
0
5
Order By: Relevance
“…Each PCR run included negative controls for PCR reagents and sample extraction. Primer pair LV-B1 were used to amplify Leishmania kDNA using methods described elsewhere ([17] and Ramirez et al, unpublished data) with the following modifications: the annealing temperature was increased to 66°C for 40 s, and a final extension at 72°C for 1 min was added. The final PCR volume was 25 μL, containing 28 ng total DNA from each sample, as determined by use of an ND-1000 spectrophotometer (Thermo Scientific NanoDrop).…”
Section: Methodsmentioning
confidence: 99%
“…Each PCR run included negative controls for PCR reagents and sample extraction. Primer pair LV-B1 were used to amplify Leishmania kDNA using methods described elsewhere ([17] and Ramirez et al, unpublished data) with the following modifications: the annealing temperature was increased to 66°C for 40 s, and a final extension at 72°C for 1 min was added. The final PCR volume was 25 μL, containing 28 ng total DNA from each sample, as determined by use of an ND-1000 spectrophotometer (Thermo Scientific NanoDrop).…”
Section: Methodsmentioning
confidence: 99%
“…Several authors have observed cross-reactions between different species (104,147), which is probably caused by the use of slightly different reaction conditions across labs and the variability of the minicircle population in each species. De Bruijn and Barker (148) reported a widely used Leishmania (Viannia)-specific PCR, validated on one strain each of 10 species, but cross-reaction of one primer with human and mouse DNAs was found (149), which could lead to false-positive results. Also, Lopez et al (150) reported a PCR that amplifies several Leishmania (Viannia) species but which was evaluated on only 5 strains.…”
Section: Kdnamentioning
confidence: 99%
“…( V. ) species. 29,30 The thermal profile was 95°C for 5 minutes, 35 cycles at 92°C for 1 minute, 66°C for 40 seconds, 72°C for 30 seconds, and a final extension at 72°C for 1 minute.…”
Section: Study Areamentioning
confidence: 99%
“…To improve the sensitivity and specificity of PCR, a chemoluminescent Southern blot was performed. 29,30 Briefly, agarose gels were processed in denaturation (1.5 M NaCl, 0.5 M NaOH) and neutralization (1 M Tris, pH 8.0, 1.5 M NaCl) buffer for 20 minutes each and blotted onto a nylon membrane (Hybond N+; Amersham Bioscience). The transfer was carried out by capillary action overnight using 10× sodium chloridesodium citrate (1.5 mol/L NaCl and 0.15 mol/L sodium citrate).…”
Section: Study Areamentioning
confidence: 99%